Atypical clinical presentation associated with Castleman disease: a case report and review of the literature - Weiwei Hu; Yuke Kong; Bianxiang Hu; Jun Ai; Peng Zhang (Frontiers in Medicine)
BackgroundCastleman disease (CD) is a group of rare and complicated diseases characterized by systemic inflammation, lymphadenopathy, and multiorgan involvement. It is often misdiagnosed as an infection, an autoimmune disease, or a malignant cancer.Case presentationIn this case, we report a 33-year-old Chinese male patient who was diagnosed with idiopathic multicentric Castleman disease (iMCD). The patient initially presented with intermittent fever and abdominal pain, followed by the development of abdominal and thoracic cavity effusions, anemia, thrombocytopenia, increased D-dimer levels, and acute kidney injury (AKI). Notably, there was an absence of significant lymphadenopathy in the early stages of disease progression. The final diagnosis was idiopathic multicentric Castleman disease (iMCD).ConclusionThis case emphasizes the importance of considering iMCD in patients with persistent fever and systemic inflammation, even in the absence of noticeable lymphadenopathy. We should monitor the progression of the disease and adopt a developmental perspective. Different stages of the disease can have different clinical manifestations. Diagnosis requires a comprehensive assessment of clinical, laboratory, and histopathological findings. The rarity and complexity of iMCD can pose diagnostic challenges, especially for healthcare providers who are not familiar with the disease, potentially leading to misdiagnosis. To prevent misdiagnosis, healthcare providers must maintain a high index of suspicion for CD in patients with prolonged fever and no significant lymph node enlargement. Timely recognition and accurate diagnosis are critical for initiating appropriate treatments and improving patient outcomes. Enhancing awareness of iMCD among healthcare providers is essential for early detection and effective management.